PENERAPAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI ERA PANDEMI COVID-19 - Utami, Risqi; Febriani, Nanda (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
The survey results of SDKI 2014 AKB in Indonesia accounted for 32/1,000 live births, the majority of which were nutritional factors of 53% pneumonia (20%), diarrhea (15%), and perinatal (15%). Colostrum is breast milk that comes out on the first day after the birth of a baby containing vitamin A, protein and immune substances that are important to protect the baby from infectious diseases and improve health quality. According to who and UNICEF in 2018, it is recommended that babies should only breast milk for at least 6 months, and breastfeeding continues until the   baby is two years old. It is Known the application of colostrum in newborns. This research uses descriptive research design, this research data is taken at PMB. Erlikasna, Amd.Keb, PMB. Veronica Sinaga, S.ST, and PMB. Suratmi, Am.Keb  in 2020, Population of this study is maternity mothers. The sampling technique was accidental sampling, the sample, number were 23 respondents, instruments used for independent variables. The Instrument were used in the form of observation sheets.  The test analysis used is frequency analysis. The results of the study from the 23 respondents who applied it found that the results for the practice of Giving Colostrum in Newborns    with Yes as many as 23 people (100%) and the results of respondents given family support as many as 21 persons (91,3%). Respondents concluded that colostrum was administered to newborns and the majority of families supported colostrum delivery in newborns. The suggestion for PMB it is expected to improve the service system specially to carry out IMD process in order to achieve colostrum delivery in newborns.